1981
DOI: 10.1017/s001447970001142x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Liming and Soil pH on Cassava (manihot esculenta) in Tropical Oligotrophic Peat

Abstract: SUMMARYIn three field experiments studying the liming needs of cassava on peat, optimum tuber DM was obtained at pH 3.8 and optimum top DM at pH 4.2; liming to higher pH values decreased tuber DM while maintaining top DM. Consequently, the Harvest Index decreased over the whole range of soil pH studied (3.49–5.50). Increases in tuber DM per hectare with liming, and with an increasing growth period, were associated with mean tuber weight (r = 0.86) and with Harvest Index (r = 0.65) rather than with tuber number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Liming to raise soil pH is therefore essential to optimize yields. In these experiments, sweet potato produced optimum tuber and vine DM at pH 5.5 (Figs 4a and b) which is comparable to the pH optima earlier obtained on peat for tobacco (5.25; Chew et al, 1980b) and sorghum (5.7; Chew et al, 1981b), but appreciably higher than for pineapple (pH 3.0-3.5; Tay, 1972) and cassava (3.8; Chew et al, 1980c), while groundnut and guinea grass are intermediate in sensitivity to peat acidity (pH optima 4.6 and 4.2, respectively; Chew et al, 1980c and1981a).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Liming to raise soil pH is therefore essential to optimize yields. In these experiments, sweet potato produced optimum tuber and vine DM at pH 5.5 (Figs 4a and b) which is comparable to the pH optima earlier obtained on peat for tobacco (5.25; Chew et al, 1980b) and sorghum (5.7; Chew et al, 1981b), but appreciably higher than for pineapple (pH 3.0-3.5; Tay, 1972) and cassava (3.8; Chew et al, 1980c), while groundnut and guinea grass are intermediate in sensitivity to peat acidity (pH optima 4.6 and 4.2, respectively; Chew et al, 1980c and1981a).…”
supporting
confidence: 86%
“…The lime treatments, quadruplicated in a randomized complete block design in each experiment, were broadcast manually and worked to about 20 cm depth in 12 X 6 m plots, sited on drained peat, newly cleared of primary jungle vegetation and undecomposed wood in the topsoil, which sample analysis showed was similar to that in earlier experiments (Chew et al, 1981a and1981b). Limed plots were made into ridges 1 m apart and about 45 cm high in which leafy terminal sweet potato shoots, each 30 cm long, were planted about 10 cm deep and 20 cm apart.…”
Section: Methodsmentioning
confidence: 99%
“…It was also concluded that 100 ppm of Cu, both as a fertilizer and mitigator of subsidence, could be added to these soils at a stabilized pH of 3.4 to 3.6 without adverse effects on plant nutrition. At lower pH, the Cu concentration of the crop was found to increase from an optimal 10 ppm to 17 (Valk 1973;Rayment and Chancey 1966;O'Toole 19'72;Mclean et al 1963Mclean et al , 1973Jasmin and Heeney 1962;Hamilton and Bernier 1973;Gupta et al 1978;Lucas et al 1974;Van Lierop et al 1980: Chew et al 1980, 1981Adams et al 19'78;Otabbong 1980;Mathur 1982b;Healy 1980 (Mills 1975 (Mathur 1982a, b;Levesque and Mathur 1982;Ma-thur Mathur et al 1919). …”
mentioning
confidence: 99%
“…According to Bolton (2009) in the investigation done within the range4-7 pH, without added P and Mg, yields of potatoes were much smaller on the more acid soils, but without K, yields were larger. Chew et al (1981) found that increased liming favored the growth of aerial parts to the detriment of tuberization of the cassava plant. Maximum yields of potatoes were obtained at a soil pH of 3.4-3.6 (4-6 t lime/ha rate) but harvest index of potato tubers (mass of tubers as percent of total dry matter produced) indicated that the 10-t/ha rate would be more suitable (Mathur and Levesque, 1983).…”
Section: Discussionmentioning
confidence: 99%